Examining Iranian physical education teachers’ perceptions of their use of Game-Based Approaches - Mohammad Maleki; Luis Miguel García López; David Gutiérrez Diaz del Campo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study was conducted to examine the extent to which the key features of Game-Based Approaches (GBAs) are used by Iranian Physical Education (PE) teachers with different genders and educational stages, and to identify the strongest predictors of whether they perceive they are teaching games using GBAs. Through an online survey, 256 PE teachers (123 women, 40.6% primary school) completed the questionnaire designed by García-López et al. (2019), which included questions on games content, planning, teaching strategies and assessment. The results showed that Iranian PE secondary school (SS) and primary school (PS) teachers, in addition to focusing on students' technical development, consider games rules as a key element. They were interested in using thematic approaches and modified games. However, the older the students, especially after the 9th grade, the lower was teachers' engagement with teaching through GBAs. SS teachers introduced more theoretical content and structural, technical and tactical elements than PS teachers. The women used GBAs in their teaching more than the men. The use of tactical problems and tactical complexity in the Iranian teachers’ lesson planning were the strongest predictors of their perception of whether they use GBAs in their teaching. The results highlight that Iranian PE teachers’ teaching style, especially in grades above 9th and in boys, must be taken into account to promote students’ technical and tactical capabilities.